Brain Activity Characteristics of Patients With Disorders of Consciousness in the EEG Resting State Paradigm: A Review - Duszyk-Bogorodzka, Anna; Zieleniewska, Magdalena; Jankowiak-Siuda, Kamila (Frontiers in Systems Neuroscience, 2022)
The assessment of the level of consciousness in disorders of consciousness (DoC) is still one of the most challenging problems in contemporary medicine. Nevertheless, based on the multitude4of studies conducted over the last twenty years on resting-state based on electroencephalography (EEG) in DoC, it is possible to outline the brain activity profiles related to both patients without preserved consciousness and minimally conscious ones. In the case of patients without preserved consciousness, the dominance of low, mostly delta, frequency and the marginalisation of the higher frequencies were observed, both in terms of global power of brain activity and in functional connectivity patterns. In turn, the minimally conscious patients revealed the opposite brain activity pattern – the characteristics of higher frequency bands were preserved both in global power and in functional long-distance connections. In this short review, we summarise the state of the art of EEG-based research in the resting state paradigm, in the context of providing potential support to the traditional clinical assessment of level of consciousness.